NMDA Receptors in Visual and Olfactory Sensory Integration in Male Long Evans Rats: A Role for the Orbitofrontal Cortex. (1st August 2020) - Sandini, Thaísa M.; Marks, Wendie N.; Tahir, Nimra B.; Song, Yuanyi; Greba, Quentin; Howland, John G.
Highlights: Systemic blockade of NMDARs impairs visual oddity tests that do and do not require sensory integration. Systemic blockade of NMDARs impairs olfactory oddity requiring sensory integration. Systemic blockade of NMDARs impairs olfactory oddity not requiring sensory integration. Intra-OFC blockade of NMDARs did not affect visual oddity requiring sensory integration. Intra-OFC blockade of NMDARs impaired olfactory oddity requiring sensory integration. Abstract: Sensory integration (SI) is a cognitive process whereby the brain uses unimodal or multimodal sensory features to create a comprehensive representation of the environment. Integration of sensory input is necessary to achieve a coherent perception of the environment, and to subsequently plan and coordinate action. The neural mechanisms mediating SI are poorly understood; however, recent studies suggest that the regulation of SI involves N-methyl-d -aspartate receptors (NMDARs) in orbitofrontal cortex (OFC). Thus, we tested this hypothesis directly in two experiments using object oddity tests that require SI for visual and olfactory stimuli. First, we blocked NMDARs with acute CPP treatment (i.p., 10 mg/kg) and tested rats in unimodal visual and olfactory SI tests, and respective control unimodal oddity tests that do not require SI. Second, we used intra-OFC infusions of AP5 (30 mM) to examine the role of NMDARs in the OFC in the oddity tests requiring SI. Systemic blockade of NMDARs impaired performance on the visual tests regardless of whether SI was required for determining oddity. In the olfactory tests, systemic treatment with CPP impaired the test requiring SI while sparing olfactory oddity, demonstrating a selective impairment in the olfactory SI. Intra-OFC blockade of NMDARs impaired olfactory SI, without effect on visual SI, demonstrating that intra-OFC NMDARs are essential for olfactory, but not visual SI. The present results are discussed in the context of the function of the OFC and its associated circuitry.